A model of asymmetric conflict outcome – Sensitivity to friction and choice of strategy in counterinsurgencies. Issue 6 (21st November 2022) - Lillbacka, Ralf
Abstract: The article assesses a model predicting outcome in counterinsurgencies based on the counterinsurgent's exposure to external friction and strategy. Unfavorable opinions, as well as insurgents' access to third-party support and sanctuaries, constitute sources of external friction. Strategies were categorized as mainly kinetic or population-centric. The model predicts: (1) counterinsurgents lose in contexts with high external friction regardless of strategy; (2) counterinsurgents applying a population-centric strategy win if external friction is low; (3) counterinsurgents applying a purely kinetic strategy win if external friction is low only by obtaining distinct tactical superiority. The model correctly predicted 27 of 30 examined cases.